The Rise of China’s Influence in Melanesian Spearhead Group (MSG): Threat to Indonesia’s Border Issues - Septyanto Galan Prakoso; Rameez Ali Surya Negara; Rheyno Reynaldi; Damar Priambodo Ahmad; Niki Wahyu Sayekti (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This article or writing aims to discuss the rising influence of China over the Melanesian Spearhead Group (MSG) which could become a potential threat to Indonesia. It was worth to note that MSG has been involved directly to the effort for West Papua. Meanwhile, Indonesia and China relation has a strained relation in the South China Sea dispute. Hence, Indonesia is now facing two problems at once, one on the northern side of its border and the other one on the eastern side of its border.  The problem is focused on how China can use the West Papua issue to pressure Indonesia regarding the South China Sea dispute by using their influence over the MSG countries. The analysis conducted in this research will analyze and explain the situation faced by the Indonesian government based on the facts. In order to approach this problem the theory of Hegemony is used. The data is collected through library research and analyzed qualitatively. This study concludes that due to China’s rising influence on the MSG, China had the much-needed leverage on Indonesia in South China Sea dispute and Indonesia is at the disadvantaged position where it has to face two problems at once those are regarding West Papua and South China Sea.